2014
DOI: 10.3346/jkms.2014.29.9.1199
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Serum Leucine-Rich Alpha-2 Glycoprotein as a Disease Activity Biomarker in Patients with Rheumatoid Arthritis

Abstract: Our study aimed to investigate whether serum leucine-rich alpha-2-glycoprotein (LRG) levels are elevated in patients with rheumatoid arthritis (RA). In addition, we assessed their correlation with disease activity parameters and pro-inflammatory cytokine, tumor necrosis factor-α (TNF-α). Our study included 69 patients with RA and 48 age- and sex-matched healthy controls. Serum concentrations of TNF-α and LRG were determined by enzyme-linked immunosorbent assay. Serum LRG concentrations were significantly eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…As secreted glycoprotein, LRG1 levels have been shown to increase in the plasma and urine of patients with a variety of cancer malignancies [26][27][28][29] and inflammatory diseases. [62][63][64][65] Our findings in the BioMe cohort, consisting of mixed races of Western patients with diabetes, indicate that plasma LRG1 is associated with renal outcome. Of note, during the preparation of this report, similar findings regarding plasma LRG1 were reported in a T2DM patient cohort in Singapore by Liu et al 66 Thus, the prognostic role of LRG1 in DKD progression has been confirmed in two separate patient cohorts, further strengthening our observations and confirming the human relevance of LRG1 in the pathogenesis of DKD.…”
Section: Discussionmentioning
confidence: 63%
“…As secreted glycoprotein, LRG1 levels have been shown to increase in the plasma and urine of patients with a variety of cancer malignancies [26][27][28][29] and inflammatory diseases. [62][63][64][65] Our findings in the BioMe cohort, consisting of mixed races of Western patients with diabetes, indicate that plasma LRG1 is associated with renal outcome. Of note, during the preparation of this report, similar findings regarding plasma LRG1 were reported in a T2DM patient cohort in Singapore by Liu et al 66 Thus, the prognostic role of LRG1 in DKD progression has been confirmed in two separate patient cohorts, further strengthening our observations and confirming the human relevance of LRG1 in the pathogenesis of DKD.…”
Section: Discussionmentioning
confidence: 63%
“…In active LN, the inflammatory and autoimmune reactions were more serious. In previous study, serum LRG1 concentrations correlated with disease activity in SLE, rheumatoid arthritis, Crohn's disease, ulcerative colitis and adult-onset Still's disease [12,20,22,24,32].…”
Section: Discussionmentioning
confidence: 80%
“…The precise function of LRG1 remains unknown, but accumulating evidences showed that LRG1 is closely correlated with various types of cancers, such as lung, oral, ovarian, gastrict, pancreatic and biliary tract cancers [14][15][16][17][18]. Moreover, LRG1 is identified as an inflammatory protein in human serum and highly expressed in various kinds of benign inflammatory and autoimmune diseases, including suspected acute appendicitis of children [19], activated ulcerative colitis [12], rheumatoid arthritis [20,21], adultonset Still's disease [22] and asthma [23]. Especially, Ahn et al found serum LRG, namely LRG1, is elevated in patients with SLE and correlates with disease activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is induced in the liver by the pro-inflammatory cytokine IL-6. 17) Further, serum levels of LRG1 are elevated in patients with rheumatoid arthritis or ulcerative colitis. 18,19) As already mentioned, elevation of preoperative serum CRP and sIL-6R levels is related to poor PCRT response in patients with resectable esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%